IMPLEMENTASI KEBIJAKAN PENERBANGAN DI BANDAR UDARA WAMENA - Silooy, Telly Nancy (JI@P, 2016)
The aim of the research to analyze the implementation of AviatiaonPolicy involving inter-organization reletionship, characteristics andcapability of implementers, organization resources and environmentcondition. The research was conducted in Jayawijaya Regency. TheMethod used was descriptive quantitative method. The method of ofobtaing the data were questionnire, interview, documentation andobservation. The sample consisted of 52 i.e 60 people. The data wereanalyzed by using frequency table through scale of lickert.Result of research reveal that implementation of aviatian policy inAirport of Wamena does not success well. This is indicated by fourindependent variables i.e. inter-organization relationship(X1) ,characteristics and capability of program implementers (X2),organization resources (X3); environment condition(X4) which is43,33. To obtain the implementation aviatian policy in airportwamena of Jayawijaya Regency optimally, the government shouldtry more communication consistency and quality by improvingknowledge and technicall skill, commitment in porfomming duty, agood control and loyality of target groups and increasing facilitiesand infrastructures.Key Words : Implementatian, Aviatian, Policy